ANALISIS STATISTICAL PROCESS CONTROL INJECTION MOULDING SEBAGAI UPAYA PENGENDALIAN KUALITAS PADA PRODUK PENAKAR DETERJEN DARI PLASTIK UKURAN ɸ 64 x 40,5 mm - Etik Puspitasari (Universitas Lambung Mangkurat, 2017)
Plastics are used to make a variety of products for example for tableware, kitchen utensils, farm equipment, bathroom equipment, toys and so on can be replaced with plastic material. The advantages of this plastic material are resistant to corrosion, its density is low enough to float, resilient and strong enough, the thermoplastic type plastic material is mostly softened at sufficiently low temperatures, has an attractive appearance and can be colored if needed.This research was conducted on plastic detergent scraper product with size ɸ64 x 40,5 mm with injection molding system using statistical quality control method and statistical process control such as control chart, pareto diagram, and fishbone used to identify and analyze product defect type and the factors that are the main cause and improvement effort so that the number of defective products can be minimized and product quality can be improved.From the research result, it was found that the optimum temperature and pressure were 200ºC and pressure 30 Bar. Where the main factor affecting the defect production of detergent scraper product of plastic with size × 64 x 40.5 mm with injection molding system is the setting of temperature and pressure must be appropriate and optimal.